Studi Deskriptif Kegiatan Kepramukaan dalam Mengembangkan Kemandirian Siswa di MIN 1 Kota Bengkulu - Tarmizi, Erwis (UNIB Press, 2024)
This research aims to describe the planning, implementation of the planning program for developing the independent attitude of scout members and evaluating/assessing the development of the independent attitude of standby scout members. The approach and type of research used is descriptive qualitative. The data sources for this research are ES (head of the madrasah), SF (teacher), AR MS AD ED MY (coach) and DV MA AF RH (standby scout member) MIN 01 Bengkulu City. Data collection techniques use observation, interviews and documentation with data credibility testing through extended observations, member checks and triangulation. The data obtained was analyzed through data reduction, data display, and drawing conclusions. The results of this research, the process of implementing scouting activities in developing the independent attitude of alert scout members, the coach plans the development of independent attitudes through integrating attitudes within the RM and designing an attitude habituation program. Then the development of the independent attitude of the alert scout members emerged in the activities of creative work, tekpram, creating chants and persari. Assessments to determine the development of students' independent behavior use behavior assessments and behavior journals.